Manajemen Rumah Sakit dalam Pencegahan Medication Error melalui Patient Safety - Mindi, Lukito; Arief Mukti Mindiroeseno (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2024)
Medication errors are preventable events which include errors in prescribing, reading a prescription (transcribing), preparing and administering drugs (dispensing), and the process of using drugs (administering). Medication errors can result in direct harm to the patient or indirectly to the hospital. The aim of this scoping review is to answer questions that have been determined from the research topic using a variety of similar research articles, then group them and draw conclusions. This research uses a scoping review approach to identify steps for developing a research protocol. Factors that cause medication errors can be prevented through good hospital management, namely patient safety, including treatment planning, electronic prescriptions, electronic medical records and medication review